Design for the real world : human ecology and social change - Papanek, Victor ([S.l.] : Thames & Hudson Ltd, 1985)
Design for the Real World has, since its first appearance twenty-five years ago, become a classic. Translated into twenty-three languages, it is one of the world's most widely read books on design. In this edition, Victor Papanek examines the attempts by designers to combat the tawdry, the unsafe, the frivolous, the useless product, once again providing a blueprint for sensible, responsible design in this world which is deficient in resources and energy.